Modeling requirements for combinatorial software testing. - Lott, C. (Software engineering notes.)
The combinatorial approach to software testing uses models to generate a minimal number of test inputs so that selected combinations of input values are covered. The most common coverage criteria is two-way, or pairwise coverage of value combinations, though for higher confidence three-way or higher coverage may be required. This paper presents example system requirements and corresponding models for applying the combinatorial approach to those requirements. These examples are intended to serve as a tutorial for applying the combinatorial approach to software testing. Although this paper focuses on pairwise coverage, the discussion is equally valid when higher coverage criteria such as three-way (triples) are used. We use terminology and modeling notation from the AETG1 system to provide concrete examples.